Strengthening tuberculosis diagnosis in a low-resource setting: experience learned in Dodoma, Tanzania - Angela Cannas; Maria Grazia Paglia; Dominick Calistus Sakhoo; Francesco Vairo; Basra Doulla; Boniface Nguhuni; Zainab Chaula; Raphael Mlumba; Maurizio Mirrione; Nazario Bevilacqua; Emanuele Nicastri; Pasquale De Nardo; et al. (Journal of Infection in Developing Countries)
Introduction: Diagnosing tuberculosis in low-resource settings mostly relies on sputum smear microscopy. Improvement through capacity building is a priority. This project aimed to strengthen tuberculosis diagnosis at an intermediate level laboratory.